2014
DOI: 10.4102/sajce.v4i1.181
|View full text |Cite
|
Sign up to set email alerts
|

Improving some cognitive functions, specifically executive functions in grade R learners

Abstract: <p>This study established the effects of a researcher-developed curriculum-based intervention programme. The intervention was grounded on principles of Feuerstein’s ideas about ‘mediated learning’. The aim of the intervention was specifically to address children’s executive functions, which are generally regarded as prerequisites for cognitive development. We studies a selected group of South African grade R learners (n = 20). A quasi-experimental design was employed to collect quantitative data on rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Peer mediation and mother-children interaction intervention effectively facilitated children with LD' CM Trabelsi et al, 2015). Esterhuizen and Grosser (2014) found that mediated learning intervention with a sample of Grade R learners enhanced cognitive functions that benefited the application of cognitive and metacognitive skills, and that eliminated motivational-affective factors that can influence learning and achievement. Tzuriel and Caspi (2017) found that peer mediation and mother-child interaction had significant effects on children's MLE strategies and CM.…”
Section: Discussionmentioning
confidence: 97%
“…Peer mediation and mother-children interaction intervention effectively facilitated children with LD' CM Trabelsi et al, 2015). Esterhuizen and Grosser (2014) found that mediated learning intervention with a sample of Grade R learners enhanced cognitive functions that benefited the application of cognitive and metacognitive skills, and that eliminated motivational-affective factors that can influence learning and achievement. Tzuriel and Caspi (2017) found that peer mediation and mother-child interaction had significant effects on children's MLE strategies and CM.…”
Section: Discussionmentioning
confidence: 97%
“…Generalmente la capacitación es a partir de talleres, y eso al parecer no es suficiente. Por falta de conocimiento y de destrezas apropiadas, los alumnos con discapacidad llevan mucho tiempo cruzando niveles de educación, a veces se quedan en un nivel durante más de dos años a partir del programa de retención (Esterhuizen y Grosser, 2014). Según Prinsloo (2006), el conocimiento insuficiente de la inclusión educativa es la causa de los problemas para su implementación porque los maestros operan con conocimientos que tienen elementos del apartheid (Makoelle, 2012).…”
Section: Contexto Del Estudiounclassified
“…Students' cognitive function, basically, does not develop naturally, but needs to be actively developed through educational process (Lövdén et al, 2020). Teachers' hard work in determining models and various learning instruments determines formation of students' cognitive function (Esterhuizen, 2014), considering a notion that suitability of student learning conditions with learning designed by teacher is able to construct conceptual thinking and reasoning patterns. Construction of conceptual mindset and reasoning is closely related to learning Mathematics materials since Mathematics fundamentally focuses on quality of thought and understanding of reason in obtaining a set of knowledge (Rocess & Ecurrent, 2018).…”
Section: Introductionmentioning
confidence: 99%